Motivasi Kerja, Loyalitas, dan Kualitas Karyawan terhadap Kinerja Karyawan PT. Varia Usaha Gresik - Sofiyah Eka Alfiyah (BISMA (Bisnis dan Manajemen), 2018)
This study to analyze the influence of work motivation, loyalty, employee quality to the employee performance in PT. Varia Usaha Gresik. The samples from this study are all permanent employees of Varia Usaha Gresik company amount to 96 employees. The sampling technique used is saturated sampling method, data analyze technique used multiple linear regression analysis with the assistance of SPSS 18.0. the study to analyze the influence of work motivation did not have a significant effect to the employee. The loyalty and employee quality significant influence to the employee performance. Work motivation, loyalty, employee quality has simultan and significant influence to employee performance.